THE COMBINATION OF α-LIPOIC ACID INTAKE WITH ECCENTRIC EXERCISE MODULATES ERYTHROPOIETIN RELEASE - Morawin, B.; Turowski, D.; Naczk, M.; Siatkowski, I.; Zembron-Lacny, A. (Biology of Sport, 2014)
The generation of reactive nitrogen/oxygen species (RN/OS) represents an important mechanism in erythropoietin (EPO) expression and skeletal muscle adaptation to physical and metabolic stress. RN/OS generation can be modulated by intense exercise and nutrition supplements such as α-lipoic acid, which demonstrates both anti- and pro-oxidative action. The study was designed to show the changes in the haematological response through the combination of α-lipoic acid intake with running eccentric exercise. Sixteen healthy young males participated in the randomised and placebo-controlled study. The exercise trial involved a 90-min run followed by a 15-min eccentric phase at 65% VO2max (-10% gradient). It significantly increased serum concentrations of nitric oxide (NO), hydrogen peroxide (H2O2) and pro-oxidative products such as 8-isoprostanes (8-iso), lipid peroxides (LPO) and protein carbonyls (PC). α-Lipoic acid intake (Thiogamma: 1200 mg daily for 10 days prior to exercise) resulted in a 2-fold elevation of serum H2O2 concentration before exercise, but it prevented the generation of NO, 8-iso, LPO and PC at 20 min, 24 h, and 48 h after exercise. α-Lipoic acid also elevated serum EPO level, which highly correlated with NO/H2O2 ratio (r=0.718, P<0.01). Serum total creatine kinase (CK) activity, as a marker of muscle damage, reached a peak at 24 h after exercise (placebo 732 ± 207 IU · L-1, α-lipoic acid 481 ± 103 IU · L-1), and correlated with EPO (r = 0.478, P<0.01) in the α-lipoic acid group. In conclusion, the intake of high α-lipoic acid modulates RN/OS generation, enhances EPO release and reduces muscle damage after running eccentric exercise.